(untitled) (Northern International Medical College Journal, 2015)
Objective : The objective of this study was to evaluate the accuracy of Fine Needle Aspiration Cytology (FNAC) in diagnosis of Papulonodular skin disease. Methodology : This prospective study was carried out in Bangabandhu Sheik Mujib Medical University (BSMMU) in the department of Dermatology and Veneral disease and department of Pathology. Study period was March 2012 to August 2012 (six months). Thirty (30) patients with papulonodular skin lesion for more than 6 weeks were enrolled. Data were collected and analysis was done by using SPSS. Results : Among 30 patients, 14 cases which were histopathologically diagnosed as epidermal inclusion cyst, pilar cyst, lipoma were also diagnosed positive by FNAC and accuracy were 100%. Rest 16 cases which were histopathologically positive as lupus vulgaris, prurigo nodularies,post kala-a zar dermal leishmaniasis, erythema nodosum, mycosis fungoides were diagnosed negative by FNAC . Overall accuracy of FNAC was only 46.7%. Conclusions : FNAC has significant limitation for diagnosis of papulonodular skin disease and not a good alternative to histopathology in diagnosis of papulonodular skin disease. Northern International Medical College Journal Vol.5(2) 2014: 342-344